The synovial fluid fibroblast-like synoviocyte: A long-neglected piece in the puzzle of rheumatoid arthritis pathogenesis - Mahmoud, Dorra Elhaj; Kaabachi, Wajih; Sassi, Nadia; Tarhouni, Lamjed; Rekik, Sonia; Jemmali, Samia; Sehli, Hela; Kallel-Sellami, Maryam; Cheour, Elhem; Laadhar, Lilia (Frontiers in Immunology, 2022)
Rheumatoid arthritis (RA) is a systemic autoimmune disease in which fibroblast-like synoviocytes (FLS) contribute to inflammation and joint destruction. FLS constitute the core component of the synovial membrane. Following inflammation of this membrane, an effusion of cell-rich synovial fluid (SF) fills the joint cavity. Unlikely, SF has been shown to contain fibroblasts with some shared phenotypic traits with the synovial membrane FLS. These cells are called SF-FLS and their origin is still unknown. They are either brought into the synovium via migration through blood vessels or they could originate within the synovium and exist in projections of the synovial membrane. The SF-FLS function and phenotype are poorly documented compared to the recently well-characterized synovial membrane FLS subsets. Furthermore, no study has yet reported a SF-FLS single-cell profiling analysis. This review will discuss the origin and cellular characteristics of SF-FLS in patients with RA. In addition, we will summarize recent advances on the involvement of SF-FLS in the pathogenesis of RA. We will also address current knowledge of the eventual relationships between SF-FLS and other types of fibroblasts, including synovial membrane FLS, circulating fibrocytes and pre- inflammatory mesenchymal (PRIME) cells. Finally, we will discuss recent therapeutic strategies employed to specifically target SF-FLS in RA.